ANALISIS SISTEM TRANSPORTASI DALAM KAMPUS UNIVERSITAS TADULAKO - Ismadarni, Ismadarni; Pradani, Novita (Jurusan Teknik Sipil Universitas Tadulako, 2017)
Tadulako University as one of the state universities in the province of Central Sulawesi has experienced rapid development. Physical growth that continues to grow along with its academic development causes the movement of traffics activity to participate in the increase. This can cause negative impacts such as high pollution levels, vehicle density and high accident rates often occur in the campus area. This study aims to analyze the transportation system within the Tadulako University Campus. It is expected that with this research it can be obtained the description of traffic problems that occurred in the campus of Tadulako University includes network system and road geometry, parking and analyzing the policies of traffic that is currently applied in the campus of Tadulako University. Traffic surveys show that motorcycle users account for 66.8% and automobiles 33.2%. Geometric survey shows that the road in the campus is relatively good because almost all roads have been structured with asphalt with one way road system. Survey on parking location also indicate that arrangement of parking space at some faculty are required so that vehicle not parked at road body. Further research is necessary to calculate the need for parking space.